Spice Defense: Resistance, Capsaicin, and Photosynthesis in Diverse Capsicum Genotypes Under Root-Knot Nematode Stress - Kansiree Jindapunnapat; Pornthip Sroisai; Nichaphat Auangaree; Nawarat Pornsopin; Suchila Techawongstien; Tanyarat Tarinta (Horticulturae)
Meloidogyne enterolobii is an aggressive root-knot nematode that poses a significant threat to global chili (Capsicum spp.) production. This study evaluated the resistance levels, physiological responses, and capsaicin accumulation patterns of diverse Capsicum genotypes—including C. annuum, C. chinense, C. frutescens, and C. baccatum—under nematode-infested and non-infested conditions. Resistance was assessed using the gall index (GI), egg per g of root, and reproductive factor (Rf). Among these evaluated parameters, Rf and egg count consistently reflected nematode reproductive success, whereas the GI proved less reliable for resistance classification. Several genotypes—notably from C. chinense and C. frutescens—exhibited strong resistance (Rf < 1), suggesting their potential for nematode-infection cultivar development. Physiological assessments revealed variable photosynthetic responses, with some genotypes showing increased photosynthetic rates of post-infection, indicating potential compensatory mechanisms. In contrast, capsaicin accumulation was influenced by nematode stress and genetic background, indicating their roles in capsaicin biosynthesis. These findings highlight the genotype-specific biochemical and physiological responses of Capsicum species to M. enterolobii infection and underscore the value of integrating physiological, biochemical, and molecular data in breeding programs. Future research should focus on dissecting hormonal signaling pathways and post-infection metabolic shifts to accelerate the development of robust, high-yielding cultivars with durable resistance.